Audit transformation through data visualization - Muhammad Alam Mauludina; Ratih Pratiwi; Eka Merdekawati; Irma Sriwijayanti; Hani Fitria Rahmani (Institute of Accounting Research and Novation (IARN), 2025)
The advancement of big data has significantly impacted various areas of business, including accounting and auditing. While numerous studies have examined the influence of big data on audit processes, research that specifically focuses on the role of data visualization remains limited. This study aims to investigate the benefits of data visualization in the context of auditing, using a qualitative approach through a case study method. The participants in this study were final-year undergraduate accounting students who had acquired basic competencies that closely align with the demands of the professional world. The findings indicate that the group supported by data visualization tools achieved higher test scores and completed tasks more efficiently compared to the group without such support. An independent samples t-test revealed a statistically significant difference between the two groups, suggesting that data visualization contributes meaningfully to more effective information processing in auditing tasks. This study contributes to the literature on accounting, accounting information systems, auditing, and the application of big data, while addressing the empirical gap concerning data visualization as a central variable in the audit field.